National Cancer Institute–Funded Social Risk Research in Cancer Care Delivery: Opportunities for Future Research. (8th September 2022) - Sanchez, Janeth I; Adjei, Brenda A; Randhawa, Gurvaneet; Medel, Josh; Doose, Michelle; Oh, April; Jacobsen, Paul B
Abstract: Background: Cancer patients and survivors with food insecurity, housing instability, and transportation-related barriers face challenges in access and utilization of quality cancer care thereby adversely impacting their health outcomes. This portfolio analysis synthesized and described National Cancer Institute (NCI)–supported social risk research focused on assessing food insecurity, housing instability, and transportation-related barriers among individuals diagnosed with cancer. Methods: We conducted a query using the National Institutes of Health iSearch tool to identify NCI-awarded extramural research and training grants (2010-2022). Grant abstracts, specific aims, and research strategies were coded for research characteristics, study population, and outcomes. Results: Of the 30 grants included in this analysis, most assessed transportation-related barriers as patient-level social needs. Grants focused on community-level social risks, food insecurity, and housing instability were largely absent. Most grants included activities that identified the presence of social risks and/or needs (n = 24), connected patients to social care resources (n = 10), and engaged community members or organizations to inform the research study (n = 9). Of the grants, 18 focused on a single type of cancer, primarily breast cancer, and more than half focused on the treatment and survivorship phases. Conclusions: In the last decade, there has been limited NCI-funded social risk research grants focused on food insecurity and housing instability. Findings highlight opportunities for future cancer care delivery research, including community and health system–level approaches that integrate social and clinical care to address social risks and social needs. Such efforts can help improve outcomes of populations that experience cancer health and health-care disparities.